Peningkatan kemampuan berbicara melalui media gambar seri di kelas III SDN. 14 Siguntur Muda Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan - Desmiyetri Desmiyetri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2018)
This research is motivated by the lack of ability of students in speaking because at the time of the learning process teachers still use the lecture method. The results showed increased student activity and teacher activity. So, it can be concluded that learning ability to speak through the media drawing series in class III SDN. 14 Young Siguntur, can improve students' speaking ability.